Atomic layer deposited high-k dielectric on graphene by functionalization through atmospheric plasma treatment. (13th March 2018) - Shin, Jeong Woo; Kang, Myung Hoon; Oh, Seongkook; Yang, Byung Chan; Seong, Kwonil; Ahn, Hyo-Sok; Lee, Tae Hoon; An, Jihwan
Abstract: Atomic layer-deposited (ALD) dielectric films on graphene usually show noncontinuous and rough morphology owing to the inert surface of graphene. Here, we demonstrate the deposition of thin and uniform ALD ZrO2 films with no seed layer on chemical vapor-deposited graphene functionalized by atmospheric oxygen plasma treatment. Transmission electron microscopy showed that the ALD ZrO2 films were highly crystalline, despite a low ALD temperature of 150 °C. The ALD ZrO2 film served as an effective passivation layer for graphene, which was shown by negative shifts in the Dirac voltage and the enhanced air stability of graphene field-effect transistors after ALD of ZrO2 . The ALD ZrO2 film on the functionalized graphene may find use in flexible graphene electronics and biosensors owing to its low process temperature and its capacity to improve device performance and stability.